Meningkatkan Keterapilan Passing bawah Melalui Latihan Drill Berpasangan Dalam Permainan Bola Voli Di Smpn 4 Cikelet - Riksandi, Sansan; Permadi, Asep Angga; Arifin, Zaenal (Jurnal Porkes, 2024)
Volleyball is a medium for developing achievements. Volleyball achievements can be started from school, namely by taking part in extracurricular activities as a forum for development and to improve the quality of the game both strategically and technically. The purpose of the identification (improving underpassing skills through paired drill exercises in volleyball games) is to increase the effectiveness of the use of underpassing. Underpassing is one of the techniques that determines the attack in a volleyball game, whether it is defending or being the start of an attack. The aim of this research is to find out how the paired drill training program influences students' underpassing technique when competing. The method used in this research is quantitative (experiment), using pre-experiment with one group pretest-posttest as a form of research design. The results of this research had an average pretest of 3.00 and posttest of 4.29. From the results of the hypothesis test, the p-value obtained is 0.000 based on the test criteria that this value is smaller than 0.05, which shows that there is a significant difference. From the results of the discussion, it can be concluded that pair drill training on bottom passing skills has a good or increasing impact so it needs to be a recommendation or an illustration that can be used by teachers, trainers, extracurricular coaches in schools to be used as a reference for research that has a good impact. Very good. This training program is suitable for improving students' lower passing techniques when competing.